Learning and Growth Dimension of the Balanced Scorecard and Its Influence on Cooperative Performance: A Study of Nawalparashi District, Nepal - Upadhyay, Jitendra Prasad; Pokhrel, Pashupati (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
The main objective of the study is to analyze the impact of learning and growth dimension on the performance of cooperative in Nepal. The